Virtual Learning Environment And The Impact On Performance Of Teacher - Felemban, Mohammad Abbas (2010)
The aim of this research is self-efficacy and creativity comparison between user teachers of virtual learning environment and non-user teachers as two components of performance, and the raising question was: Is there any difference between-efficacy and creativity as two components of performance in the user teachers of the virtual learning environment and non-user teachers of the virtual learning environment?